P6 A proforma to improve the acute management of traumatic anterior shoulder dislocations to meet published national standards for treatment. (8th April 2021) - Donovan, Richard L; Abdelmalek, Amir; Crowther, Mark A A; Packham, Iain
Abstract: Background: BESS/BOA Patient Care Pathways provide national guidelines for the acute management of traumatic anterior shoulder dislocations with respect to emergency reduction and follow-up assessment. COVID-19 posed increased challenges in terms of analgesia choice and altered follow-up arrangements. This study aimed to assess adherence to the care pathway and improve patient care. Methodology: We retrospectively analysed all acute traumatic anterior shoulder dislocations at the MTC in Bristol. We collected data during 01/04/2019-31/05/2019 and 01/04/2020-31/05/2020 to analyse the quality of their management. Data parameters collated included examinations and imaging performance, choice of analgesia, follow-up rates, and physiotherapy referrals. Results: We identified 32 patients in 2019, and 24 in 2020. Full neurovascular examinations pre- and post-reduction were poorly documented. Peri-reduction imaging utilization was near 100%. Referral to follow-up was 88% in 2019 but 38% in 2020. Of those assessed in clinic during COVID-19, fewer were mobilised early or referred to outpatient physiotherapy. Conclusions: We have created a proforma/prompt to improve the quality of the management of these injuries, and successfully liaised with the Emergency Department for this to be included in their documentation. This proforma improves documentation quality, access to follow up and physiotherapy. During a 'second wave' we encourage patient access to BESS online resources.